Bifunctional CdS@Co9S8/Ni3S2 catalyst for efficient electrocatalytic and photo-assisted electrocatalytic overall water splitting. Issue 6 (21st January 2020) - Si, Fangyuan; Tang, Chengyang; Gao, Qiongzhi; Peng, Feng; Zhang, Shengsen; Fang, Yueping; Yang, Siyuan
Abstract : Bifunctional CdS@Co9 S8 /Ni3 S2 for efficient electrocatalytic and photo-assisted electrocatalytic overall water splitting with 86.5% electrical-to-hydrogen ( η ETH ) and 5.72% solar-to-hydrogen ( η STH ) conversion efficiencies. Abstract : The production of green hydrogen energy from water splitting driven by electric or solar energy is of great interest nowadays. The development of highly efficient, stable, and noble-metal-free bifunctional electrocatalysts has sparked a huge surge in investigation in the field of electrocatalytic (EC) water splitting. Herein, an original 1D core@2D branch CdS@Co9 S8 /Ni3 S2 electrode is prepared in situ on Co/Ni alloy foam through a simple one-pot hydrothermal process. The binder-free, self-supported CdS@Co9 S8 /Ni3 S2 is demonstrated to be a low-cost and highly efficient bifunctional electrocatalyst for both the hydrogen evolution reaction (HER) and the oxygen evolution reaction (OER) in alkaline solution. The optimal CdS@Co9 S8 /Ni3 S2 electrode exhibits excellent bifunctional HER and OER properties with quite low overpotentials of 69.6 and 285 mV required to reach EC currents of −10 and 20 mA cm −2, respectively. Moreover, using the CdS@Co9 S8 /Ni3 S2 electrode as both the anode and cathode, the assembled electrolyzer only required a 1.56 V cell voltage to reach a current density of 10 mA cm −2 . Significantly, it was also found that such a metal foam-supported photocatalyst/electrocatalyst electrode can effectively realize dual model incorporated photo-assisted electrocatalytic overall water splitting, which delivers a 174.1% higher H2 production rate than that of electrocatalysis only. This work may open a new avenue for the synergistic use of solar energy and electric energy in the production of hydrogen from water splitting.